The role of psychosocial factors on perceived impact of oil 'scrambling' in the Niger-delta: a community's experience (2009)
The Niger Delta Region of Nigeria has been plagued with recurrent crisis emanating from perceived injustice, degradation and neglect of residents in such areas. For example, violent reactions from militant youths have become unpredictable and uncontrollable; a situation that has rendered the region volatile and stressful. This study investigated the influence of personal and social variables such as locus of control and social support on adjustment to stressful life event resulting from incessant crisis. A total of two hundred subjects drawn from a violence-ridden community participated in the quantitative study. The findings indicated that females perceived their experiences to be more stressful than males, those with internal locus of control reported less stressful experience than those with external locus of control, while residents who had stayed in such environments for a longer time experienced lower stress than those on shorter time. The findings' of the study highlighted the importance of psychosocial factors in alleviating the impact of stress and programs to develop locus of control and strengthen the social support of people in crisis ridden environments.